Enhanced mechanically induced red-light emitting novel mechanoluminescence materials for ultrasonic visualization and monitoring applications. Issue 18 (25th January 2021) - Fan, Yu-Ting; Yang, Yun-Ling; Li, Ting; Yuan, Jia-Yong; Li, Qian-Li; Zhao, Jing-Tai; Wan, Dong-Yun; Zhang, Zhi-Jun
Abstract : When Ca 2+ is substituted with Sr 2+, the optical band gap of (Ca, Sr)ZnOS:Mn 2+ becomes narrower and the trap depths becomes deeper, which leads to ML enhanced. The monitoring of ultrasonic intensity was achieved by using this ML material. Abstract : Mechanoluminescent (ML) materials have become a novel and excellent fluorescent material in the field of luminescence for demonstrating potential applications in stress detection, biological imaging and optical displays. Through some trivial modifications between the constituent atoms and the crystal structures, these luminescent materials exhibit different ML performances for various applications. Herein, a series of novel red emitting Mn 2+ -activated (Ca, Sr)ZnOS shows strong fluorescence emission under the mechanical actions of compression or ultrasonic effect. The traps in (Ca, Sr)ZnOS:Mn 2+ become deeper and the optical band gap decreases from 3.75 to 3.15 eV with the increase of the Sr 2+ content. It is worth noting that the ML intensity of Ca0.7 Sr0.3 ZnOS:Mn 2+ is about one order of magnitude stronger than that of CaZnOS:Mn 2+ under the same conditions. The enhanced ML performance can be attributed to the fact that when the trap depths become deeper, the trap energy level greatly increases. In addition to conventional stress monitoring, (Ca, Sr)ZnOS:Mn 2+ was successfully used for determining the ultrasonic intensity distribution through ML. The work not only provides a facile and effective method for facile synthesis of (Ca, Sr)ZnOS:Mn 2+ solid solution, but also demonstrates its extraordinary ML properties and applications in the field of ultrasound monitoring.